Drivers, barriers and impacts of digitalisation in rural areas from the viewpoint of experts - Ferrari, Alessio; Bacco, Manlio; Gaber, Kirsten; Jedlitschka, Andreas; Hess, Steffen; Kaipainen, Jouni; Koltsida, Panagiota; Toli, Eleni; Brunori, Gianluca (Information and software technology, 2022)
The domain of rural areas, including rural communities, agriculture, and forestry, is going through a process of deep digital transformation. Digitalisation can have positive impacts on sustainability in terms of greater environmental control, and community prosperity. At the same time, it can also have disruptive effects, with the marginalisation of actors that cannot cope with the change. When developing a novel system for rural areas, requirements engineers should carefully consider the specific socio-economic characteristics of the domain, so that potential positive effects can be maximised, while mitigating negative impacts. The goal of this paper is to support requirements engineers with a reference catalogue of drivers, barriers and potential impacts associated to the introduction of novel ICT solutions in rural areas. To this end, we interview 30 cross-disciplinary experts in digitalisation of rural areas, and we analyse the transcripts to identify common themes. According to the experts, main drivers are economic, with the possibility of reducing costs, and regulatory, as institutions push for more precise tracing and monitoring of production; barriers are the limited connectivity, but also distrust towards technology and other socio-cultural aspects; positive impacts are socio-economic (e.g., reduction of manual labour, greater productivity), while negative ones include potential dependency from technology, with loss of hands-on expertise, and marginalisation of certain actors (e.g., small farms, subjects with limited education). This paper contributes to the literature with a domain-specific catalogue that characterises digitalisation in rural areas. The catalogue can be used as a reference baseline for requirements elicitation endeavours in rural areas, to support domain analysis prior to the development of novel solutions, as well as fit-gap analysis for the adaptation of existing technologies. •We interview 30 cross-disciplinary experts in the field of digitalisation of rural areas.•We classify 14 barriers, 15 drivers, and 10 types of impact related to the adoption of digital technologies.•Main drivers are towards adoption are economic and regulatory, with institutions playing a crucial role.•Main barriers are socio-cultural, and the limited connectivity.•Positive impacts are socio-economic, while negative ones are the marginalisation of actors and loss of hands-on expertise. [Display omitted]